It Will All End In Tears - Jesper Just; Octavio Zaya (Madrid; La Casa Encendida, 2008)
The exhibition It Will All End In Tears, the first individual show dedicated to the artist Jesper Just (Copenhagen, 1974) in Spain, takes its title from one of the five films chosen by the curator Octavio Zaya, which together with Bliss and Heaven, Some Draughty Window, Something to Love and A Vicious Undertow completes the show and explores the main themes treated by Jesper Just: gender as a social and cultural construct rather than biological, and the generation gap, specifically centred on the father-son relationship.
English
Keywords: N4390-5098 Visual Arts- Exhibitions